English in early childhood: bilingual education in Brazil - Giovana Maria Carvalho Martins; Thereza Cristina de Souza Lima (Revista Linguística, 2022)
This article aims to discuss about early childhood education and bilingualism in Brazil. The focus is on English teaching and Brazilian bilingual schools. It addresses the acquisition of the English language in early childhood, discussing child development and childhood (EDWARDS; GANDINI; FORMAN, 2016; IVERSON, 2010), bilingualism and discussions about language acquisition (MOZZILLO, 2015; VIAN JR; WEISSHEIMER; MARCELINO, 2013; MEGALE, 2005), about the bilingual child (MARTINS, 2007) and also about bilingual schools and bilingualism in Brazil (FILIZOLA, 2019; MOURA, 2016). The methodology used was the bibliographic review, developing the investigation through the analysis and discussions of several authors. The research theme started from the experience of one of the authors with bilingual education in early childhood, and from the need to demystify and understand the importance of acquiring a second language in childhood. The children were considered as active agents of their learning and as powerful subjects, and the language as a form of expression of these children in the context in which they are inserted.